THE EFFECTIVENESS OF USING PICTURES TO IMPROVE STUDENTSâ SPEAKING SKILL - Episiasi, Episiasi; Ardayati, Ardayati; Novianti, Sinta (JURNAL SMART, 2015)
AbstractÂ The problem of this study was âIs it significantly effective to use pictures to improve studentsâ speaking skill to the sixth semester students of English Education Study Program at STKIP PGRI Lubuklinggau?â. This study was conducted to find out whether it is significantly effective to use pictures to improve studentsâ speaking skill. There were two hypotheses; null hypotheses (H0) and alternative hypotheses (Ha). The sample of the study was 23 students which were taken through cluster random sampling. Research method of this study was pre-experimental with one group pre-test and post-test design. The writer used speaking test and analyzed the data by using conversion of score range, individual score, and match t-test. Based on the result of data analysis, it was found out that studentsâ average score in the pre-test was 46.43 and post-test was 60.54. Finally, the results of matched t-test calculation shows that the t-obtain was higher than t-table. The t-obtained was 31.37 while the t-table was 1.717. It means that the null hypotheses (Ho) was rejected and automatically the alternative hypotheses (Ha) was accepted. It can be concluded that it is significantly effective to teach speaking skill by using pictures.Â Keywords: Effectiveness, Speaking, Picture